Azide–Tetrazole Equilibrium of C-6 Azidopurine Nucleosides and Their Ligation Reactions with Alkynes - Lakshman, Mahesh K. (2010)
[Image: see text] Facile syntheses of C-6 azidopurine ribonucleosides and 2′-deoxyribonucleosides have been developed. For silyl and acetyl protected as well as unprotected nucleosides, access to the azido derivatives could be readily attained via displacement of BtO(−) from the O(6)-(benzotriazol-1-yl)inosine nucleosides by azide anion. Use of diphenylphosphoryl azide/DBU as a simple route to the acetyl-protected azido nucleosides was also evaluated, but this proved to be inferior. Since these azido nucleosides can exist in an azide•tetrazole equilibrium, the effect of solvent polarity on this equilibrium was investigated. Subsequently, a detailed analysis of Cu-mediated azide-alkyne (“click”) ligation was undertaken. Biphasic CH(2)Cl(2)/H(2)O medium proved to be best for the ligation reactions, suppressing the undesired azide reduction that was competing. Interestingly, although the tetrazolyl isomer predominates (ca 80%) in CD(2)Cl(2) and in CD(2)Cl(2)/D(2)O, the Cu-catalyzed click reactions proceed smoothly with the silyl-protected ribo and 2′-deoxyribonucleosides, leading to the C–6 triazolyl products in good to excellent yields. Thus, depletion of azido form from the reaction mixture shifts the azide•tetrazole equilibrium, eventually resulting in complete consumption of azide and tetrazole. In several cases, major and minor azide-alkyne ligation products were observed and characterization data are provided for both. In order to confirm the regiochemistry leading to the major isomer, one product was crystallized and evaluated by X-ray crystallography. The Cu-catalyzed azide-alkyne ligation is clearly efficient and significantly superior to thermal reactions, which were slow. Biological evaluation showed low cytotoxicities for the agents, suggesting their usefulness as biological probes.